1995
DOI: 10.1111/j.1365-4362.1995.tb00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Lupus Erythematosus: Comparison of Direct Immunofluorescence Findings With Histopathology

Abstract: Although DIF is an extremely useful diagnostic tool, it should always be used in conjunction with histopathology and the combination of the two methods yields the best results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Negative DIF in skin biopsies in these four cases is probably due to biopsy of late presenting lesions where immune complexes are not demonstrable or due to some technical problems already mentioned. [4,5] And also, it is the experience of the authors that in treated SLE the skin biopsy may show no immune deposits. However, three additional patients were given a diagnosis of SLE by DIF primarily along with concomitant detection of ANA in our laboratory.…”
Section: Cytoid Body Positivitymentioning
confidence: 95%
“…Negative DIF in skin biopsies in these four cases is probably due to biopsy of late presenting lesions where immune complexes are not demonstrable or due to some technical problems already mentioned. [4,5] And also, it is the experience of the authors that in treated SLE the skin biopsy may show no immune deposits. However, three additional patients were given a diagnosis of SLE by DIF primarily along with concomitant detection of ANA in our laboratory.…”
Section: Cytoid Body Positivitymentioning
confidence: 95%
“…54 Pohle, Tuffanelli, 55 studying 16 patients with DLE and 12 with SLE, two of which did not present cutaneous lesions, found positive DIF in 93.7% and 100% of lesions, respectively. Four out of eight cutaneous fragments, without apparent changes, obtained from patients with SLE, were found to be simultaneously positive for IgG and IgM.…”
Section: Direct Immunofluorescencementioning
confidence: 92%
“…Al-Suwaid et al, 54 studying 18 patients with DLE, found positive DIF in 72.7% of lesions, with a predominance of IgG (77.8%), accompanied by IgM, IgA or complement, or in isolation in 27.7%. A homogenous pattern for IgG deposit occurred in 55.5% of cases.…”
Section: Direct Immunofluorescencementioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, it is mandatory to correlate DIF results with both clinical presentation and histopathological findings. [47] Up to 95% of individuals with DLE show LBT. However, positive DIF findings in DLE are confined to lesional skin, whereas skin with or without lesions can give positive DIF findings in SLE.…”
Section: Linear Iga Dermatosismentioning
confidence: 99%